Optimalisasi Sitem Informasi Manajemen Pendidikan Di Madrasah - Muthmainnah Muthmainnah (CV. Lenggogeni Data Publishing, 2023)
This research is to find out the optimization of management information systems. And also to know how the process of data collection. This research method uses a qualitative research method with a descriptive approach. This research was conducted at the Jabalnur Paloh Lada Private Madrasah Aliyah, Dewantara District, North Aceh Regency. This article uses by collecting data related to data collection in madrasas. The sources of informants in this study were the school principal and teaching staff at the madrasah. The results of this study indicate that a management information system or SIM can make it easier for teacher staff, students or student guardians to find out the information in the madrasah.